Korelasi Penerapan Pertanian Berkelanjutan dengan Manusia Sebagai Khalifah di Bumi - Zuhrufi Indana Husna (An Nahdhoh Jurnal Kajian Islam Aswaja, 2022)
This study aims to determine the application of sustainable agriculture with the role of humans as caliphs on earth. The problem obtained is that the implementation of Sustainable Agriculture has not been running effectively and efficiently, considering that farmers are more concerned with profit oriented. Farmers do not pay attention to the excessive use of pesticides and drugs which are the cause of environmental damage and degradation of natural resources, considering that humans are caliphs fil ard who have an obligation to protect the earth that God has entrusted to humans. The research methodology was carried out with a quantitative approach using Spearman rank correlation analysis. The results of the analysis show that a correlation coefficient of 0.565 means that there is a positive (unidirectional) and quite strong relationship between the application of sustainable agriculture and the role of humans as caliphs on Earth.